2020
DOI: 10.5853/jos.2019.03440
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiologic and Therapeutic Perspectives Based on Thrombus Histology in Stroke

Abstract: Recent advances in endovascular thrombectomy have enabled the histopathologic analysis of fresh thrombi in patients with acute stroke. Histologic analysis has shown that the thrombus composition is very heterogeneous between patients. However, the distribution pattern of each thrombus component often differs between patients with cardiac thrombi and those with arterial thrombi, and the efficacy of endovascular thrombectomy is different according to the thrombus composition. Furthermore, the thrombus age is rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 74 publications
(122 reference statements)
2
58
1
Order By: Relevance
“…Moreover, patients treated with tPA who underwent thrombectomy presented higher platelet fraction in thrombi. This fact has not been previously described but has been suggested in some studies ( 43 ). A paradoxical platelet activation has been reported secondary to fibrinolysis ( 44 ) as responsible for delayed thrombosis in some patients with tPA-resistant thrombi causing reocclusion and rethrombosis ( 45 ).…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, patients treated with tPA who underwent thrombectomy presented higher platelet fraction in thrombi. This fact has not been previously described but has been suggested in some studies ( 43 ). A paradoxical platelet activation has been reported secondary to fibrinolysis ( 44 ) as responsible for delayed thrombosis in some patients with tPA-resistant thrombi causing reocclusion and rethrombosis ( 45 ).…”
Section: Discussionsupporting
confidence: 57%
“…It is worth noting that thrombus composition plays a crucial role in recanalization therapy in LAO patients ( 13 ). We found that the percentage of fibrin in the VHD group was significantly higher than that in the other groups, and the contents of red blood cells and WBCs were lower.…”
Section: Discussionmentioning
confidence: 99%
“…The pathomechanism of NBTE remains unknown. Autopsy studies in patients with NBTE have shown that cardiac vegetation is mainly composed of platelets [ 21 ], and examinations of thrombi retrieved during mechanical thrombectomy in stroke patients with NBTE have indicated very high platelet and low erythrocyte fractions [ 11 , 22 ]. These studies suggest that platelet-mediated mechanisms play a key role in the development of cancer-associated NBTE.…”
Section: Discussionmentioning
confidence: 99%